3D food printing: Applications of plant-based materials in extrusion-based food printing. Issue 26 (12th September 2022) - Wang, Mingshuang; Li, Dongnan; Zang, Zhihuan; Sun, Xiyun; Tan, Hui; Si, Xu; Tian, Jinlong; Teng, Wei; Wang, Jiaxin; Liang, Qi; Bao, Yiwen; Li, Bin; et al.
Abstract: As an emerging digital production technology, 3D food printing intends to meet the demand for customized food design, personalized nutrition, simplification of the food supply chain system, and greater food material diversity. Most 3D food printing studies focus on the development of materials for extrusion-based food printing. Plant-based foods are essential for a healthy diet, and they are growing in popularity as their positive effects on human health gain wider recognition. The number of original studies on plant-based printable materials has increased significantly in the past few years. Currently, there is an absence of a comprehensive systematic review on the applications of plant-based materials in extrusion-based food printing. Thus, this review aims to provide a more intuitive overview and guidance for future research on 3D printing of plant-based materials. The requirements, classifications, and binding mechanisms of extrusion-based food printing materials are first summarized. Additionally, notable recent achievements and emerging trends involving the use of plant-based materials in extrusion-based food printing are reviewed across three categories, namely, hot-melt (e.g., chocolate), hydrogel, and soft (e.g., cereal- and fruit/vegetable-based) materials. Finally, the challenges facing 3D food printing technology as well as its future prospects are discussed.